Development and validation of the ethnic trust scale in China - Li, Yaning; Yang, Yisheng; Liu, Junying; Wang, Pai; Mao, Zheng (Frontiers in Psychology, 2024)
Background Considerable research has shown that ethnic trust reflects the existence of friendly relations among all ethnic groups and ethnic individuals, and can help in resolving ethnic conflicts and contradictions, promoting exchanges among various ethnic groups, which is highly relevant to social stability. Methods This research, including three studies, aimed to explore the conceptual structure of ethnic trust in China, and develop and validate a measurement of the ethnic trust scale. In the first study, we used free association and in-depth interview methodology, applied cluster analysis, multidimensional scaling analysis, and grounded theory to construct the theoretical framework of Chinese people’s ethnic trust concept. In the second study, we constructed an initial inventory based on the concept dimensions of ethnic trust established in the first study. We screened items by item analysis and extracted common factors using exploratory factor analysis (EFA), thus determining a total of 48 items in the two subscales (interpersonal-oriented ethnic trust subscale and the intergroup-oriented subscale), which consisted of two dimensions including particular trust and universal trust. In the third study, we used first-and second-order confirmatory factor analysis (CFA) to test the scale’s construct validity. Results The results indicated a good fit between the two-factor model and the data. And the ethnic trust scale showed very good internal consistency (Cronbach alpha >0.89) and test-retest reliability >0.70. Discussion Based on our results, have formed a ethnic trust scale by keeping 48 items, which can beused to measure the levels of interpersonal-oriented and group-oriented ethnic trust within the Chinese cultural context.